Teaching Classical Languages Worldwide: Successes, Challenges, and Perspectives (Based on Teaching Classics Worldwide): None - Dumitru Oancea, Maria-Luiza (Didactica Danubiensis, 2026)
Our study, Teaching Classical Languages Worldwide: Successes, Challenges, and Perspectives, examines the global state of Latin and Ancient Greek instruction and explains why classical language education remains culturally and civically significant. It identifies effective practices, persistent inequalities, and strategies for sustainable growth and broader participation. The paper builds primarily on the edited volume by Steven Hunt and John Bulwer, Teaching Classics Worldwide: Successes, Challenges and Developments, which provides a comparative framework and relevant international examples for our analysis. Our research also draws on comparative international scholarship, synthesizing existing studies and experiences concerning curriculum reform, access, and institutional support. It contributes to ongoing debates about moving from the traditional grammar-translation method toward cultural and communicative approaches. A comparative, descriptive framework combines historical review with regional case studies and an examination of policies, programs, and collaborations across Europe, the United States, Israel, and Australia. The study highlights increasing curricular diversification, successful outreach initiatives, and productive partnerships among schools, universities, and civic organizations. Nevertheless, unequal access and shortages of qualified teachers remain major barriers. Digital technologies enhance engagement, motivation, and assessment. Overall, the findings guide educators, researchers, and administrators in shaping equitable, sustainable, and modern models of classical language education worldwide.